Synthesis, molecular and crystal structure analysis of 2-bromo-4-chloro-6-{[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-hydrazonomethyl}-phenol by experimental methods and theoretical calculations - Guntepe, Feyizan; Saracoglu, Hanife; Caliskan, Nezihe; Yuksektepe, Cigdem; Cukurovali, Alaaddin (Elsevier, 2012)
A novel hydrazone derivative 2-bromo-4-chloro-6-{[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-hydrazonomethyl}-phenol was synthesized and characterized by IR, UV-Vis spectroscopy and X-ray single crystal diffraction. The compound crystallizes in monoclinic space group P2(1)/c with a = 8.0862(3) angstrom, b = 7.6168(1) angstrom, c = 37.3168(12) angstrom and beta = 91.186(1)degrees. In addition, the molecular geometry and vibrational frequencies of the title compound in ground state have been calculated by using density functional theory (DFT) at B3LYP level with 6-31G and 6-31G(d,p) basis sets. The geometrical parameters of the title compound obtained from XRD studies are in good agreement with the calculated values. The analysis of IR spectrum supported by OFF calculations was particularly devoted to the manifestations of hydrogen bonding in the nu(str)(N-H) and nu(str)(O-H) vibrations. To determine the conformational flexibility for a selected torsion angle tau(C6-C1-C7-N1) one-dimensional potential energy scan was performed using AM1 in the full range of 0-360 degrees increasing of 10 degrees. UV-Vis absorption spectrum of the compound has been compared to theoretical spectrum (vertical excitations) computed by time dependent density functional theory (TD-DFT). Besides frontier molecular orbitals and molecular electrostatic potential map analysis were investigated by theoretical calculations. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Hydrazone; Crystal structure; IR spectroscopy; DFT calculation